DIDACTIC ASPECTS OF THEORETICAL FUNDAMENTALS OF LEADERSHIP IN THE SOCIO-PHILOSOPHICAL SPHERE - Zarychanskyi, O.; Zarichanska, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article considers theories of leadership, which were considered by scientists at different times and in the context of different worldviews, which allows us to conclude that the concepts of "leader" and "leadership" are closely interrelated, especially the goal, because leadership is a challenge for something important, it is a challenge with passion, it is a desire for a goal. A leader’s competence is the level of maturity required to perform a specific job, the amount of knowledge and skills he uses to achieve a goal or solve problems. In addition, and this is a key point for our study, competent leadership can be learned, it is necessary to learn, and throughout life. Thus, the development of leadership practice has been significantly influenced by value theories. By focusing on the meaning of the activities of the leader and his followers, they have proved in theory and in practice that the leadership that modernity needs can only be responsible. A leader, if he wants to remain a person, must be responsible to himself, to his followers, to society and to his future. It is proved that a leader is not just a person who, on the way to his socialization, has acquired certain qualities of a leader, but has found himself in the right place and at the right time. The essence of leadership qualities can be revealed only during the performance of socially significant activities. It is under such conditions that people show activity and the person who acted as a generator of ideas and organizer of transformational activities will retain leadership functions. Also in the transition to the information society, leadership begins to be perceived as a team game, in which each participant performs extremely important and necessary work and the leader, as a team captain, is just a good performer, who got his role through the coach and circumstances, often accidental him.